2011
DOI: 10.1002/bmb.20552
|View full text |Cite
|
Sign up to set email alerts
|

Non‐native english language speakers benefit most from the use of lecture capture in medical school

Abstract: Medical education in the United States and Canada continues to evolve. However, many of the changes in pedagogy are being made without appropriate evaluation. Here, we attempt to evaluate the effectiveness of lecture capture technology as a learning tool in Podiatric medical education. In this pilot project, student performance in an inaugural lecture capture-supported biochemistry course was compared to that in the previous academic year. To examine the impact of online lecture podcasts on student performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 16 publications
(18 reference statements)
0
44
0
Order By: Relevance
“…Shaw and Molnar (2011) examined the impact of lecture capture in a medical school course. Their study found no correlation between final course grades and the number of times students accessed lectures.…”
Section: Previous Researchmentioning
confidence: 99%
“…Shaw and Molnar (2011) examined the impact of lecture capture in a medical school course. Their study found no correlation between final course grades and the number of times students accessed lectures.…”
Section: Previous Researchmentioning
confidence: 99%
“…T here is a sizeable body of literature about the education of "English as a second language" (ESL) students in health sciences; [1][2][3][4] however, much of this information addresses ESL students in English speaking countries. There is less information about the challenges faced by ESL students studying health sciences in English in non-English speaking countries.…”
Section: Advances In Knowledge -"English As a Second Language" (Esl) mentioning
confidence: 99%
“…Files can take the form of either audio only or audio combined with video, with research showing that students prefer the latter (Embi, Biddinger, Goldenhar, Schick, Kaya & Held, 2006). Lecture capture describes the multimedia capturing of live lectures before an audience of students in higher education, and while this phrase is sometimes used synonymously with other terms including podcasting and vodcasting (for examples of the use of these terms, see Shaw & Molnar, 2011;Vajoczki, Watt, Marquis, & Holshausen, 2010). According to Cambridge Dictionaries Online, a podcast is more accurately defined as an audio-only recording ("Podcast", n.d.) while a vodcast is a video recording ("Vodcast", n.d.).…”
mentioning
confidence: 99%